(untitled) (Texas Journal of Philology, Culture and History, 2025)
Since the dawn of human self-awareness to the modern era of technology, one of the consistently evolving and relevant fields of scientific inquiry has been the study and analysis of text. This article examines the historical development and key approaches in the field of text analysis. It highlights the stages of text analysis from ancient civilizations to contemporary computational linguistics and natural language processing (NLP) technologies. The contributions and methodologies of renowned scholars such as Wilhelm Wundt, Vladimir Propp, Claude Shannon and Noam Chomsky are analyzed. The article provides extensive insights into the principles, methods, and applications of text analysis in NLP, machine learning, and information technologies